Ssams2, a Gene Encoding GATA Transcription Factor, Is Required for Appressoria Formation and Chromosome Segregation in Sclerotinia sclerotiorum - Liu, Ling; Wang, Qiaochu; Zhang, Xianghui; Liu, Jinliang; Zhang, Yanhua; Pan, Hongyu (Frontiers in Microbiology, 2018)
AMS2, a multicopy suppressor for the cpn1 (SpCENP-A) mutant, functions as a transcription factor (TF) to specifically regulate histone genes transcription and chromatin segregation. As one of the well-conserved TFs in eukaryotic organisms, little is known about the roles of AMS2 protein in the filamentous fungi. In Sclerotinia sclerotiorum, one of the notorious plant fungal pathogens, there are nine proteins predicted to contain GATA-box domain according to GATA family TF classification, among which Ssams2 (SS1G_03252) encodes a protein including a GATA-box domain. Here, we characterized the roles of Ssams2 in the developmental process and fungal virulence by using RNA interference (RNAi)-based gene silencing in S. sclerotiorum. Ssams2-silenced strains with significantly reduced Ssams2 gene expression levels exhibited defect in hyphal growth, hyphal branching patterns, compound appressoria differentiation and the oxalic acid production compared to the wild-type (WT) strain. Results of infection assays on common bean (Phaseolus vulgaris) leaves indicated that Ssams2 is required for full virulence in S. sclerotiorum during infection in the susceptible host plants. Furthermore, the numbers of cell nucleus in the same length of mycelium in Ssams2-silenced transformants were significantly less than that in the WT strain. The expression levels of histone genes and cell cycle genes in transformants were down-regulated significantly in the RNAi strains. Collectively, our results suggest that the TF SsAMS2 is required for growth, appressoria formation, virulence and chromosome segregation in S. sclerotiorum.